The failure on the effectiveness of formalin on cadaver disinfection and alternative methods - AKSU, MEHMET BURAK; ÖZKAN, MAZHAR; ŞEHİRLİ, ÜMİT SÜLEYMAN (My University, 2023)
Objective: It was aimed to identify the contaminant and determine the alternative disinfectant detection in the microbial growth observed in various parts of the cadaver stored in the formalin tank in the dissection laboratory of Marmara University Anatomy Department. We also performed a literature review of this unusual pathogen. Materials and Methods: Swab samples were inoculated on agar mediums. After incubation, matrix-assisted laser desorption ionizationtime of flight mass spectrometry (MALDI-TOF MS) analysis was used to identify the isolate from the detected uniform colonies. Sample solution from the cadaver tank, freshly prepared 5% formalin and 0.55% ortho-phthalaldehyde were used to determine the disinfectant sensitivity of the isolate. Results: According to 16s rDNA sequence analysis, it was concluded as Skermanella aerolata with 99% similarity. In the disinfectant susceptibility test, it was observed that S. aerolata and control bacteria could grow in 5% formalin taken from the cadaver tank. No growth was detected in other disinfectants. Conclusion: To prevent cadaver contamination in anatomy laboratories, the quality control of the embalming solutions and indoor air filtration of the dissection rooms should be checked at regular intervals. Members of Skermanella genus have been identified as environmental organisms in several studies, however, recent researches reported this bacterium as a human pathogen.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; Skermanella aerolata; Cadaver; Anatomy; Formalin; SKERMANELLA-AEROLATA; ANATOMY; LARGOMOBILIS; NOV.; Skermanella aerolata; Cadaver; Anatomy; Formalin